2020
DOI: 10.1186/s13071-020-04490-8
|View full text |Cite
|
Sign up to set email alerts
|

IPSE, a urogenital parasite-derived immunomodulatory molecule, suppresses bladder pathogenesis and anti-microbial peptide gene expression in bacterial urinary tract infection

Abstract: Background Parasitic infections can increase susceptibility to bacterial co-infections. This may be true for urogenital schistosomiasis and bacterial urinary tract co-infections (UTI). We previously reported that this co-infection is facilitated by S. haematobium eggs triggering interleukin-4 (IL-4) production and sought to dissect the underlying mechanisms. The interleukin-4-inducing principle from Schistosoma mansoni eggs (IPSE) is one of the most abundant schistosome egg-secreted proteins an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is well known that the emotional stress associated with cancer, trauma, and blood loss due to prolonged surgery can suppress the immune response in perioperative patients [12]. In addition, studies have shown that parasitic infections increase the susceptibility to co-infected bacteria [13]. In this case, it is also possible that tapeworm infections increase the immunocompromised patient's susceptibility to conditionally pathogenic bacteria.…”
Section: F I G U R E 1 Patient's Preoperative Computer Tomography Sca...mentioning
confidence: 99%
“…It is well known that the emotional stress associated with cancer, trauma, and blood loss due to prolonged surgery can suppress the immune response in perioperative patients [12]. In addition, studies have shown that parasitic infections increase the susceptibility to co-infected bacteria [13]. In this case, it is also possible that tapeworm infections increase the immunocompromised patient's susceptibility to conditionally pathogenic bacteria.…”
Section: F I G U R E 1 Patient's Preoperative Computer Tomography Sca...mentioning
confidence: 99%
“…IPSE [92] binds to immunoglobulins, with a high affinity for IgE [88]. Once IPSE binds to IgE-bound FceRI receptors on the surface of basophils, it triggers the release of IL-4 and IL-13 [89,93], which directly induces the differentiation of monocytes into the alternatively activated macrophage-like M2 phenotype.…”
Section: Hepatic Schistosomiasismentioning
confidence: 99%